Online Learning during the Covid-19 Pandemic: A Web-Based Survey of Undergraduate Students of Pokhara University, Nepal (Quest Journal of Management and Social Sciences, 2021)
Background: COVID-19 pandemic has forced educational institutions throughout the world to shut, putting academic calendars in jeopardy. To continue the academic activities, most educational institutions have switched to online mode of learning.Objective: Against this backdrop, the study aims to identify the perception and attitude of the undergraduate students towards e-learning during Covid-19 pandemic, to determine the online learning characteristics of the students across different academic year, and to explore the factors that influence the online learning activities of the students.Method: The study employed a descriptive cross-sectional research design. The self-administered questionnaire was developed after a thorough assessment of the literature and consultation with topic specialists, and it included demographic information about the research participants, as well as their perceptions and attitudes regarding online classes. The questionnaire was created on Google Forms, and the link was distributed to the students of all the four schools through Viber and Messenger groups. Data was collected online from 300 undergraduate students at Pokhara University in Nepal. Descriptive statistics (frequency, percentage) and inferential statistics were used to examine and interpret the data. The Chi-squared test was employed to analyze the link between the student’s online learning characteristics and academic year. To discover the characteristics that impact online learning activities, exploratory factor analysis was performed.Result: The results indicated statistically significant association of online learning characteristics of students of different academic year with availability of alternative power source, internet service, digital platform used and availability of basic computer skill and continuation of online class. Majority of the students evinced a positive attitude towards online classes. Online learning was deemed advantageous since it offered learners with flexibility and convenience. Furthermore, teachers devote appropriate time to studying, motivate students to learn, and emphasize student-centered learning. However, students are dissatisfied with the teachers’ online teaching skills owing to a lack of training and familiarity with modern information technology.Conclusion: The study concluded that although students reported positive attitude towards online classes, there are serious challenges of power backup or alternative power supply, poor connectivity, unfamiliarity of digital platforms and poor ICT skills among students. Teachers need to be trained properly for the effective and productive teaching and learning along with proper handling of digital platforms. The school/ college/ university must have a well-established IT infrastructure for the smooth operation of online classes.